Response of unilamellar DPPC and DPPC:SM vesicles to hypo and hyper osmotic shocks: A comparison. (May 2015) - Ahumada, M.; Calderon, C.; Alvarez, C.; Lanio, M.E.; Lissi, E.A
Highlights: Osmotic shocks applied to vesicle suspensions, promote changes in turbidity and an increase in fluorescence intensity of entrapped dyes. Calcein leakage is slower than the osmotic driven water influx/outflux, particularly after hypertonic shock. Osmotic response of liposomes are determined by its size. Abstract: DPPC and DPPC:SM large unilamellar vesicles (LUVs), prepared by extrusion, readily respond to osmotic shocks (hypo- and hyper-osmotic) by water influx/efflux (evaluated by changes in turbidity) and by entrapped calcein liberation (measured by an increase in dye fluorescence intensity). On the other hand, small unilamellar vesicles (SUVs) prepared by sonication are almost osmotically insensitive. LUVs water transport, both in hypo- and hyper-osmotic conditions, takes place faster than calcein ejection towards the external solvent. Similarly, response to a hypotonic imbalance is faster than that associated to a hypertonic stress. This difference is particularly noticeable for the increase in calcein fluorescence intensity and can be related to the large reorganization of the bilayer needed to form pores and/or to adsorb the dye to the inner leaflet of the vesicle after water efflux. Conversely, addition of SM to the vesicles barely modify the rate of calcein permeation across the bilayer.